The relationship between deprivation and alcohol-related presentation at Accident and Emergency (A&E) over a three-month period. Issue 2 (May 2015) - Dolan, R; Paterson, B
Objectives: To identify any relationship between deprivation and the level of presentation to Accident and Emergency with alcohol-related conditions in a busy East Coast teaching hospital in Scotland. Methods: Over an 87-day-period initial screening to determine whether alcohol played a part in each presentation was conducted at triage. These patients were then streamed according to their Paddington Alcohol Test (Pat) score into Pat +ve and Pat −ve groups. The postcode of each patient was recorded before they were assigned deprivation levels using the DepCat scoring system. This information was then compiled in Microsoft Excel 2003 and a graph showing the differences in the number of presentations across the social spectrum was constructed. Results: Nine hundred and forty four patients were screened as attending due to alcohol with 43.86% being Pat +ve and 56.14% being Pat −ve. Overall 66.42% of the Pat +ve group and 54.42% of Pat −ve were from deprived or very deprived areas. Conclusions: The use of electronic-based screening was effective at highlighting patients presenting to Accident and Emergency with alcohol-related problems, and these presentations highlighted a direct link between the level of deprivation and attendances.